Physical activities, exercises, and their effects to the immune system - Nurmasitoh, Titis (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Every systems in human body correlate to maintain homeostasis. One of those systems which contribute to maintain homeostasis is the immune system. The immune system defends physiological functions against foreign substances and cancer cells through a complex and multilayered mechanism. The ability to defend against foreign substances and abnormal cells is done by two types of immune system, which are Innate immune system and adaptive/acquired immune system. There are also certain factors that affect the immune system, for instance physiological factor, nutrition, psychological factor, environental factor, and exercise or physical activities. Regular exercises and physical activities with moderate intensity will boost the immune system. Sedentary lifestyle and minimal physical activity will increase the risk of infectious diseases. While exercises and physical activity with high intensity will suppress the immune system hence increase the risk of infection.